The Health of Women in Latin America and the Caribbean - Levine, Ruth; Glassman, Amanda; Schneidman, Miriam (Washington, DC: World Bank, 2013)
This study has two main objectives: 1) to analyze trends and differences in women's health, examples of good practices in delivery and financing of women's health programs; and the key dimensions of women's health that are relevant for the health reforms currently underway in Latin America; and 2) to provide guidance for governments and program designers in addressing the most pressing causes of women's ill health, within the context of broader sectoral and national policies. The report is divided into five sections. This overview highlights the rationale for focusing on the topic of women's health, along with a conceptual framework for understanding the determinants of women's health and the role of health policy. Chapter 1 describes major trends and differentials in women's health in Latin America and the Caribbean, grouping countries into four broad categories according to trends in health, demographic, and socioeconomic indicators. Chapter 2 turns to a discussion of success, utilization, and spending on women's health, providing the results of new analyses for seven countries. Chapter 3 provides an overview of the links between women's health and health reform. It emphasizes potential synergies and opportunities to integrate women's health concerns in broader reform initiatives and points out risks to be avoided. The final chapter presents concluding remarks and recommendations.